Students’ Interaction in Asynchronous Blended Learning: The Analysis of Community of Inquiry Framework Implementation - Rizki Farani (UICELL, 2019)
The purpose of this study is to describe students’ interaction in asynchronous blended learning as a part of community of inquiry activities. This research is self-observational study in ICT-based course for pre-service English teachers. There were 91 students who participated in blended learning activities. Data were obtained from offline teaching journals and online activities in Google Classroom Platform. The data were analyzed by using community of inquiry framework to describe social, cognitive presence and teaching presence. The findings showed that offline activities provided more social presence, cognitive presence and teaching presence. Meanwhile, online activities only provided teaching presence and cognitive presence without strong social presence. The implication of this research is students attend the online learning as a part of required instruction in the course only, not because of self-awareness of building knowledge. Keywords: interaction, asynchronous Blended Learning, community of Inquiry framework